Orphaning Regimes: The Missing Link Between Flattened and Penetrating Slab Morphologies - Grima, Antoniette Greta; Lithgow-Bertelloni, Carolina; Crameri, Fabio (Frontiers in Earth Science, 2020)
Slab orphaning is a newly discovered phenomenological behaviour, where the slab tip breaks off at 660 km depth and is abandoned by its parent slab. Upon orphaning, subduction continues uninterrupted through the lateral motion of the parent slab above 660 km depth. In this work, we present a regime diagram for the range of conditions under which slabs can orphan at mid-mantle depths. We observe that a viscosity jump at 1000 km, separate from the endothermic phase change responsible for the 660 km seismic discontinuity, is necessary for orphaning, as is slab and mantle weakening between 660 and 1000 km. We show that orphan slabs, similar to other deep slab morphologies, can be the end result for a wide range of physical parameters governing slab dynamics: Slab orphaning persists across wide variations in slab dip, slab strength, Clapeyron slope and overriding plate nature. The diversity in orphan slab sizes and orphaning length scales is tied to the orphaning regime space, which describes a hitherto unexplored region between deflected and penetrating deep-subduction modes that can be found in the transition zone between upper and lower mantle. Orphaning provides a simple dynamic link between the well known deflection and penetration, and provides one possible way for subducting slabs to switch from direct penetration to deflection, littering the mantle with abandoned fragments.